2022
DOI: 10.3390/medicina58101443
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Women and Men with Psoriasis: A Cross-Sectional Questionnaire-Based Study

Abstract: Background and objectives: Psoriasis can lead to feelings of stigmatization, hinder social functioning, and impair quality of life. Psoriasis can also affect sexual activity, but there is still little research on this topic. The present study investigated whether and to what extent psoriasis, its severity, location and extent of skin lesions affect sexual dysfunction. Materials and Methods: A total of 45 women and 64 men aged 18 to 73 years hospitalized for psoriasis exacerbations were included in the study. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…No correlation between erectile dysfunction and the presence of such lesions was also found by Wojciechowska-Zdrojowy or Cabete et al In our study, almost half of the patients had lesions in the anogenital area but there was no correlation with FSFI or IIEF scores. Opposite results were reported by Kędra et al who observed that the severity of sexual problems was associated with the lesions in the genital area, but also on the face or hands, not with the IIEF-5 (5-question version of IIEF) score ( 39 ).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…No correlation between erectile dysfunction and the presence of such lesions was also found by Wojciechowska-Zdrojowy or Cabete et al In our study, almost half of the patients had lesions in the anogenital area but there was no correlation with FSFI or IIEF scores. Opposite results were reported by Kędra et al who observed that the severity of sexual problems was associated with the lesions in the genital area, but also on the face or hands, not with the IIEF-5 (5-question version of IIEF) score ( 39 ).…”
Section: Discussionmentioning
confidence: 74%
“…In our study, we did not assess psoriasis activity and severity index (PASI) since it was an online survey however in other experiments the results are diversified. In the paper by Kędra et al there was a correlation between sexual problems and PASI in both sexes ( 39 ) and in the paper by Wojciechowska-Zdrojowy et al – in men ( 27 ). Kwan et al assessed only body surface area (BSA) affected with lesions and found a significant difference in sexual function between patients with BSA more or less than 10 ( 36 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another study by Gupta et al had similar results, which documented that 40.8% of the study participants had reported having their sexual lives impacted by psoriasis. [12] Kędra et al also reported that approximately 80% had an affected sexual life due to the skin lesions, and more than 50% at least sometimes avoided sexual contact [13].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the head and the upper extremities are visible body regions and, therefore, their involvement has been reported to be associated with higher feelings of stigmatization and levels of social anxiety [ 18 ]. The trunk includes the genitals, and genital involvement has been shown to impact patients’ intimate relationships [ 19 ].…”
Section: Discussionmentioning
confidence: 99%